Toolbox of teaching strategies - Pan Lei; Xi Hui-Qin; Shen Xiao-Wei; Zhang Chen-Yu (Sciendo, 2018)
A teaching strategy is a method, which can help students to gain knowledge, deliver information, and improve their learning. Different learning environments, such as clinical teaching, online teaching, and face-to-face traditional learning environments, require different teaching strategies for students. Choosing teaching strategies for a course is very important for nurse educators because various factors should be taken into account to make students meet the learning outcomes. The use of modern technologies in teaching strategies can improve students' competencies and confidences. The purpose of this article is to create a toolbox integrating ten teaching strategies that can be used in different teaching environments.